Easy material lab testing - Azzmi, Norazura Mizal; Hashim, Siti Zubaidah; Mohd Noor, Norehan@Norlida; Jamaludin, Nazhatulzalkis; Ahzahar, Nadira; Zakaria, Intan Bayani (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
Lab work is a hands-on activity that enhances students' skills. Therefore, it was introduced at the beginning of the course under the title Construction Materials and Material Properties, so that first semester students are exposed to different types of materials and tests related to construction industry. For this reason, the idea of developing progressive learning methods was born to replace conventional methods. Using Google Forms, the sample concept was developed by integrating the course requirement summary and the content of each lab test. The information is supported by pictures, tables or diagrams and a brief paragraph to enhance the student's understanding of the purpose and method of the test being designed. The Google Form is designed like a quiz, contains a quick feedback mechanism to score sections and answers, and takes less than five minutes to complete. Additionally, targets, equipment and materials lists, including observation results, were posted on a Google form. This method allows students to quickly choose the correct answer instead of listening to a summary in the usual mode appreciation to the one-way communication of online distance learning (ODL). A questionnaire survey was conducted to collect responses from students, respectively from the first semester of the survey degree. Analysis of the results shows that the feedback is very positive and proves that students' ability to understand the lesson increases rapidly when applying the Easy Material Lab Test format. This statement was supported by 100 respondents who answered questions related to construction materials and laboratory testing, of which 58% received top scores.